Music of the Spheres in Akbarian Sufism - Rašić, Dunja (Religions, 2022)
As per tradition, no human could hear the music of the spheres save for Pythagoras. Ibn ʿArabī, however, claimed he heard this music each time he prayed sincerely. This article examines how the Pythagorean concept of the music of the spheres came to be integrated and reinterpreted in Akbarian Sufism, with a special emphasis on Ibn ʿArabī’s notion of samāʻ and the modes of recreating the music of the spheres in Sufi gatherings.